Thermoelectric cooling materials - Mao, Jun; Chen, Gang; Ren, Zhifeng (Nature materials, 2021)
Solid-state thermoelectric devices can directly convert electricity into cooling or enable heat pumping through the Peltier effect. The commercialization of thermoelectric cooling technology has been built on the Bi 2 Te 3 alloys, which have had no rival for the past six decades around room temperature. With the discovery and development of more promising materials, it is possible to reshape thermoelectric cooling technology. Here we review the current status of, and future outlook for, thermoelectric cooling materials. Thermoelectric materials can generate electricity from waste heat but can also use electricity for cooling. This Perspective discusses coefficients of performance for these systems and the state-of-the-art for materials, and suggests strategies for the discovery of improved thermoelectric materials.